ENVIRONMENTAL PROBLEMS OF UKRAINE DURING THE WAR PERIOD: WAYS OF THEM OVERCOMING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article presents environmental problems of Ukraine. Attention is focused on the problems of the natural environment, which existed before (the Chernobyl disaster, disposal of radioactive waste, processing and cleaning of mixers, pollution of water resources, etc.) and greatly worsened due to military actions. In addition, a number of new environmental threats associated with war are listed. The territory of Ukraine is subjected to bombardment and destruction every day, one by one, once inhabited cities and villages disappear from the map, leaving behind either a burnt ruin, the products of combustion of which rise into the atmosphere and spread around the world, or a putrid supply, the products of which decay enter the soil and with underground water or vapors pose an irreparable threat to the entire environment and health. The article emphasizes ecological migrations caused by the war. In the first place in Ukraine is the safety of the population, protection against enemy attack for the preservation of life. Unfortunately, environmental problems have receded into the background, but they are not devalued, but remain promising on the way to victory. The Ministry of Environmental Protection and Natural Resources of Ukraine keeps statistics of environmental damage caused to Ukraine due to the war. Considering their depth and irreparability, these problems will have to be solved for more than a dozen years. And this, in turn, sets priority tasks that can already be solved today in the safer territories of our country. The publication highlights international connections and projects that contribute to the improvement of the ecological state and will be able to ensure the restoration of the environment in the post-war period. The article presents a survey of the population of Vinnytsia, Khmelnytskyi and Lviv regions regarding their actions to overcome the environmental crisis; implemented measures and prospective programs contributing to the improvement of the environment are presented. Attention is drawn to modern environmental education and volunteer nature protection activities of citizens of Ukraine.